Organizational Culture Influences, Work Motivation on Employee Performance (Study at Kimpraswil (Regional Housing and Infrastructural Office) Agency of Riau Province) - Asmara Hendra Komara (Jurnal Aplikasi Manajemen, 2011)
This research objectives is to test and analyze the effect of organizational culture, work motivation on employee performance. This research presents some theoretical concept of organizational behavior, leadership, organizational culture, organization strategy, motivation and performance. Its sample consist of 120 respondents as public employee in the Regional Housing and Infrastructural Office environment, Province of Riau. Data analysis make use a Structural Equation Modeling (SEM), with application of the Analysis of Moment Structures (AMOS) 4.01. Results of the research between independent and dependent variables showed that (1) organizational culture has significant and positive impact on employee performance, (2) organizational culture has also significant and positive impact on employee performance.Keywords: organizational culture, work motivation, and employee performance.